2017
DOI: 10.1088/1367-2630/aa69e7
|View full text |Cite
|
Sign up to set email alerts
|

Group chasing tactics: how to catch a faster prey

Abstract: We propose a bio-inspired, agent-based approach to describe the natural phenomenon of group chasing in both two and three dimensions. Using a set of local interaction rules we created a continuous-space and discrete-time model with time delay, external noise and limited acceleration. We implemented a unique collective chasing strategy, optimized its parameters and studied its properties when chasing a much faster, erratic escaper. We show that collective chasing strategies can significantly enhance the chasers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 43 publications
0
51
1
Order By: Relevance
“…Juveniles, less than 10-15 years of age [80,81] would still be in the zone where their long legs could be used to maximize top speed, potentially helping run down faster prey items. Beyond this it has been shown that amongst pack hunting animals employing strategy or communication between individuals can allow them to capture prey that is faster than any one individual [82]. Combining these factors we find that pack hunting would only increase the energetic savings differential even more dramatic between tyrannosaurs compared to allosauroids.…”
Section: Plos Onementioning
confidence: 69%
“…Juveniles, less than 10-15 years of age [80,81] would still be in the zone where their long legs could be used to maximize top speed, potentially helping run down faster prey items. Beyond this it has been shown that amongst pack hunting animals employing strategy or communication between individuals can allow them to capture prey that is faster than any one individual [82]. Combining these factors we find that pack hunting would only increase the energetic savings differential even more dramatic between tyrannosaurs compared to allosauroids.…”
Section: Plos Onementioning
confidence: 69%
“…We now test that an extension of the same model to groups of moving animals gives the increased spatial cohesion typically observed in experiments. Our model draws from extensive work on collective motion [ 44 48 ] but, in contrast to most previous studies, our individuals do not react directly to each other. Instead, individuals estimate the quality of all points within a given maximum distance using a many-options version of the Bayesian model.…”
Section: Resultsmentioning
confidence: 99%
“…Juveniles, less than 10-15 years of age [68,69] would still be in the zone where their long legs could be used to maximize top speed, potentially helping run down faster prey items. Beyond this it has been shown that amongst pack hunting animals employing strategy or communication between individuals can allow them to capture prey that is faster than any one individual [70]. Combining these factors we find that pack hunting would only increase the energetic savings differential even more dramatic between tyrannosaurs compared to allosauroids.…”
Section: Why Tyrannosaurids?mentioning
confidence: 69%